Requirements elicitation for robotic and computer-assisted minimally invasive surgery. (19th August 2019) - Nakawala, Hirenkumar; De Momi, Elena; Tzemanaki, Antonia; Dogramadzi, Sanja; Russo, Andrea; Catellani, Michele; Bianchi, Roberto; De Cobelli, Ottavio; Sideridis, Aristotelis; Papacostas, Emmanuel; Koupparis, Anthony; Rowe, Edward; et al.
The robotic surgical systems and computer-assisted technologies market has seen impressive growth over the last decades, but uptake by end-users is still scarce. The purpose of this article is to provide a comprehensive and informed list of the end-user requirements for the development of new generation robot- and computer-assisted surgical systems and the methodology for eliciting them. The requirements were elicited, in the frame of the EU project SMARTsurg, by conducting interviews on use cases of chosen urology, cardiovascular and orthopaedics procedures, tailored to provide clinical foundations for scientific and technical developments. The structured interviews resulted in detailed requirement specifications which are ranked according to their priorities. Paradigmatic surgical scenarios support the use cases.